Categorization Features of the Concept of «Sacrament» by Active Adult Internet Users - Medvedskaia, Elena (Problemi sučasnoï psihologìï (Online), 2021)
The aim of the article is to analyze the specifics of categorization of abstract concepts by adults who use different information sources: traditional / printed and innovative / digital. Methods. An author used a questionnaire method with the open-ended type of questions as the primary tool to study the choice of the preferred information codin g system by adults. To reconstruct the categorical structure of the respondents’ consciousness in their understanding of the concept «sacrament», the method of the semantic differential was used. The differential includes 40 adjectives, which form 7 categories of an average consciousness according to their factorial structure («Assessment», «Strength», «Activity», «Complexity», «Orderliness», «Reality» and «Usuality»). The above categories have been established in a previous study of individuals of different age groups and cultures. Results of the research. The results of a comparative analysis of the category structure and the meaning of the concept «Sacrament» are contained in two groups of adults: the reading subjects and the active Internet users. It is determined that the cognitive complexity of consciousness of the web users is lower than the one of the reading subjects, according to two parameters: 1) decreasing of categories’ quantity that form the concept; 2) simplifying the organization of the category, represented by only one pole. For the active Internet users, the content of the concept «sacrament» is close to the «secret». Conclusions. The empirical data proves the tendency to simplify the categorization in understanding the abstract concepts of active Internet users. This allows designating a new scientific-practical issue of cognitive deformation of adults as the effect of Internet exposure.